1980
DOI: 10.1056/nejm198009113031101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Supportive Companion on Perinatal Problems, Length of Labor, and Mother-Infant Interaction

Abstract: We studied the effects of a supportive lay woman ("doula") on the length of labor and on mother-infant interaction after delivery in healthy Guatemalan primigravid women. Initial assignment of mothers to the experimental (doula) or control group was random, but controls showed a higher rate (P less than 0.001) of subsequent perinatal problems (e.g. cesarean section and meconium staining). It was necessary to admit 103 mothers to the control group and 33 to the experimental group to obtain 20 in each group with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
0
12

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(168 citation statements)
references
References 11 publications
3
153
0
12
Order By: Relevance
“…Multiple studies have provided evidence of the positive influences that mothers experience when receiving labor support from a companion present during birth (Campero et al, 1998;Sosa, Kennell, Klaus, Robertson, & Urrutia, 1980;Zhang, Bernasko, Leybovich, Fahs, & Hatch, 1996). One recent study revealed that mothers who received continuous support from an experienced woman during labor and birth had fewer medical interventions and requested less pain medication (Hodnett, 2002).…”
Section: Social Supportmentioning
confidence: 99%
“…Multiple studies have provided evidence of the positive influences that mothers experience when receiving labor support from a companion present during birth (Campero et al, 1998;Sosa, Kennell, Klaus, Robertson, & Urrutia, 1980;Zhang, Bernasko, Leybovich, Fahs, & Hatch, 1996). One recent study revealed that mothers who received continuous support from an experienced woman during labor and birth had fewer medical interventions and requested less pain medication (Hodnett, 2002).…”
Section: Social Supportmentioning
confidence: 99%
“…Emotional support decreases forceps frequencies [10,23] and involves trust, which has been shown to be an essential component of nursing practice [17] and hence we believe for midwifery practice too.…”
Section: Forceps and Neonatal Outcomementioning
confidence: 89%
“…there are unpleasant consequences like insomnia, delayed in initial attachment between mother and newborn, and improper breast feeding position of mothers (28,29). Evidence shows that the prevalence of perinea trauma is lower among women who gave birth at home, because they are mentally and physically are prepared for the birth and the environment is attractive and comfortable for the mother; so they get along with the physiological process, without hurrying, which creates a sense of security as home environment can help healthy perinea (30).…”
Section: Discussionmentioning
confidence: 99%